Kemampuan Representasi Matematika dalam Pembelajaran Matematika - Fadilla, Siti; Wandini, Rora Rizki (Lembaga Yasin AlSys, 2024)
Mathematical Representation Ability is an ability that students need to transform mathematical problems into other forms. Because representation skills are one of the keys to mathematical communication skills. Mathematical representation ability is one of the mathematical skills that students are required to have. Representations provide support to students in understanding mathematical concepts and their relationships. This research aims to explore mathematical representation abilities. This research uses a qualitative descriptive method which systematically presents data obtained from literature studies.